Mechanistic home range analysis reveals drivers of space use patterns for a non‐territorial passerine. Issue 12 (10th August 2020) - Ellison, Natasha; Hatchwell, Ben J.; Biddiscombe, Sarah J.; Napper, Clare J.; Potts, Jonathan R.
Abstract: Home ranging is a near‐ubiquitous phenomenon in the animal kingdom. Understanding the behavioural mechanisms that give rise to observed home range patterns is thus an important general question, and mechanistic home range analysis (MHRA) provides the tools to address it. However, such analysis has hitherto been principally restricted to scent‐marking territorial animals, so its potential breadth of application has not been tested. Here, we apply MHRA to a population of long‐tailed tits Aegithalos caudatus, a non‐territorial passerine, in the non‐breeding season where there is no clear 'central place' near which birds need to remain. The aim is to uncover the principal movement mechanisms underlying observed home range formation. Our foundational models consist of memory‐mediated conspecific avoidance between flocks, combined with attraction to woodland. These are then modified to incorporate the effects of flock size and relatedness (i.e. kinship), to uncover the effect of these on the mechanisms of home range formation. We found that a simple model of spatial avoidance, together with attraction to the central parts of woodland areas, accurately captures long‐tailed tit home range patterns. Refining these models further, we show that the magnitude of spatial avoidance by a flock is negatively correlated to both the relative size of the flock (compared to its neighbour) and the relatedness of the flock with its neighbour. Our study applies MHRA beyond the confines of scent‐marking, territorial animals, so paves the way for much broader taxonomic application. These could potentially help uncover general properties underlying the emergence of animal space use patterns. This is also the first study to apply MHRA to questions of relatedness and flock size, thus broadening the potential possible applications of this suite of analytic techniques. Abstract : The authors extend techniques of mechanistic home range analysis by novel application to a population of long‐tailed tits, a cooperatively breeding bird. In doing so, they uncover details of the movement mechanisms leading to observed segregated home range patterns. These include memory of conspecific interactions, habitat selection, flock size and relatedness.